Quantificação e avaliação ambiental da contaminação por metais e arsênio em sedimentos da bacia do Rio Doce - MG - Camila Vidal Alves Santolin (2015)
The Doce River Basin (DRB) is located in southeastern Brazil, and several economic activities are performed along its entire length, including mining, agriculture and food industry. The mining activity involves the exploration of a range of minerals, in additionto gold mining in which mercury is used to increase the extraction efficiency. The quality of water in the basin has been monitored since 1997 by the state agency for environmental control. However, there are few publications about metals in sediments of this basin. This work investigated 8 metals and As in sediments from19 points of DRBin three different sampling periods. The study was divided into five steps for better environmental assessment of the basin. In the first stage, it was carried out physicochemical characterization of the sediments, identifying them as sandy mineral, rich in aluminosilicate and oxy-hydroxides of Fe and Mn, with low cation exchange capacity. In the second step, it was determined the total concentrations of the elements Al, As, Cr,Cu, Fe, Hg, Mn, Ni and Zn, and physical and chemical parameters. It was observed that 47% of determinations are above the acceptance limits for sediment established by national Resolution CONAMA nº 344/2004, especially for Cr, across all basin. The partial cold extraction with 1 mol L-1 HCl in the Step 3 was performed to identify the availability of environmental factors investigated, with the metals Cu, Mn and Zn appear larger in labilities of DRB points. The fourth step involved the environmental assessment of DRB through geochemical parameters and chemometric data analysis. The geochemical parameters quality, geoaccumulation index (Igeo) and enrichment factor (EF), werecalculated identifying Cr, Cu, Ni and Zn as possibly from anthropogenic sources of contamination, generally in DRB, and As in localized points. Statistical analysis using PCA and HCA identified Zn from waste dumps in the basin rivers, As and Hg associated with oxy-hydroxides of Mn and Fe, and Ni, Cr and Cu in clay containing Al. Finally, in the fifthstep the qualitative and quantitative speciation of Hg was performed by TDAAS and DMA, verifying the predominant species in the oxidized form in DRB, with a few spots containing relevant amount of reduced species, indicating contamination by recent elementary Hg. In general, DRB are impacted by Cr, Cu, Ni and Zn, and As and Hg localized. Through this study, ten points of the basin were considered the most affectedby the investigated elements, in different combinations and ratios.